The Relationship Between Knowledge and Attitudes of Pregnant Women and the Incidence of Hyperemesis Gravidarum at the Tangeban Community Health Center, Masama District, Banggai Regency - Istiqomah, Nur; Syahriani, Syahriani; Qadhawijayanti , Suci; Sukri, Muhammad; Ariani Saputri , Chandra (Yayasan Inspirasi El Burhani, 2025)
Introduction: Hyperemesis gravidarum is a condition of excessive nausea and vomiting that occurs in the first trimester of pregnancy. It can cause dehydration, electrolyte imbalances, weight loss, and even affect fetal growth if not properly managed (Ministry of Health of the Republic of Indonesia, 2023). In Indonesia, based on the Indonesian Health Profile (2023), the prevalence of HEG is reported to be around 1–3% of all pregnancies, with higher cases occurring in young pregnant women and primigravidas. Objective: To determine the relationship between knowledge and attitudes of pregnant women with the incidence of hyperemesis gravidarum at the Tangeban Community Health Center, Masama District, Banggai Regency. Method: This study used an observational analytical design with a cross-sectional approach. The sample in this study was 34 pregnant women respondents. The sampling technique used total sampling. The instrument used was a questionnaire. Data analysis used univariate and bivariate data. Result: Univariate analysis showed that the majority of pregnant women who experienced hyperemesis gravidarum were 21 people (61.8%), had a good level of knowledge about hyperemesis gravidarum, namely 22 respondents (64.7%), and had a positive attitude towards hyperemesis gravidarum as many as 24 respondents (70.6%). Bivariate analysis showed a relationship between knowledge and the incidence of hyperemesis gravidarum in pregnant women at the Tangeban Community Health Center, Masama District (p-value 0.040), and there was a relationship between attitude and the incidence of hyperemesis gravidarum in pregnant women at the Tangeban Community Health Center, Masama District (p-value 0.020). Conclusion: There is a relationship between knowledge and attitude and the incidence of hyperemesis gravidarum in pregnant women at the Tangeban Community Health Center, Masama District.